Pengembangan Permainan Educaplay sebagai Media Pengayaan pada Mata Pelajaran PPh Pasal 21 Perpajakan Kelas XI Akuntansi SMK Negeri di Surabaya - Amanda Putri Nadila; Susanti (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
The implementation of enrichment programs for students who have met learning proficiency standards still faces challenges, particularly the lack of variety in the teaching materials used. A preliminary study at State Vocational High Schools 1, 4, 6, and 10 in Surabaya showed that enrichment activities for the subject “Income Tax Article 21” still rely on practice exercises via Google Forms or student workbooks, making them less engaging and leading to student burnout. A total of 63% of students stated that the tax material was quite difficult to understand, while 93% of students hoped for more engaging and enjoyable innovations in enrichment media. Based on this phenomenon, this study aims to develop the Educaplay game as an enrichment medium for Income Tax Article 21 material, specifically the calculation of the Average Effective Rate (AER), as well as to determine the level of feasibility and student response to this medium. The study employed a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), involving subject matter experts, media experts, and 20 11th-grade Accounting students from four public vocational high schools in Surabaya. The instruments used included a review questionnaire, a Likert scale validation sheet, and a Guttman scale student response questionnaire, all analyzed using quantitative descriptive methods. The results showed that the development of the educational media was carried out systematically through all stages of the ADDIE model, with a feasibility rating of 95.83% from subject matter experts and 98.47% from media experts (classified as “Highly Feasible”), as well as a student response rate of 97.86% (classified as “Very Good”). These findings imply that the Educaplay game is suitable as an interactive enrichment medium to enhance student motivation and engagement in tax education.